The orthotic and therapeutic effects following daily community applied functional electrical stimulation in children with unilateral spastic cerebral palsy: A randomised controlled trial - Pool, D.; Valentine, J.; Bear, N.; Donnelly, C.; Elliott, Catherine; Stannage, K. (2015)
Background: The purpose of this study was to determine the orthotic and therapeutic effects of daily community applied FES to the ankle dorsiflexors in a randomized controlled trial. We hypothesized that children receiving the eight-week FES treatment would demonstrate orthotic and therapeutic effects in gait and spasticity as well as better community mobility and balance skills compared to controls not receiving FES. Methods: This randomized controlled trial involved 32 children (mean age 10 yrs 3 mo, SD 3 yrs 3 mo; 15 females, 17 males) with unilateral spastic cerebral palsy and a Gross Motor Function Classification System of I or II randomly assigned to a FES treatment group (n = 16) or control group (n = 16). The treatment group received eight weeks of daily FES (four hours per day, six days per week) and the control group received usual orthotic and therapy treatment. Children were assessed at baseline, post FES treatment (eight weeks) and follow-up (six weeks after post FES treatment). Outcome measures included lower limb gait mechanics, clinical measures of gastrocnemius spasticity and community mobility balance skills.Results: Participants used the FES for a mean daily use of 6.2 (SD 3.2) hours over the eight-week intervention period. With FES, the treatment group demonstrated a significant (p < 0.05) increase in initial contact ankle angle (mean difference 11.9° 95 % CI 6.8° to 17.1°), maximum dorsiflexion ankle angle in swing (mean difference 8.1° 95 % CI 1.8° to 14.4°) normalized time in stance (mean difference 0.27 95 % CI 0.05 to 0.49) and normalized step length (mean difference 0.06 95 % CI 0.003 to 0.126) post treatment compared to the control group. Without FES, the treatment group significantly increased community mobility balance scores at post treatment (mean difference 8.3 units 95 % CI 3.2 to 13.4 units) and at follow-up (mean difference 8.9 units 95 % CI 3.8 to13.9 units) compared to the control group. The treatment group also had significantly reduced gastrocnemius spasticity at post treatment (p = 0.038) and at follow-up (dynamic range of motion mean difference 6.9°, 95 % CI 0.4° to 13.6°; p = 0.035) compared to the control group. Conclusion: This study documents an orthotic effect with improvement in lower limb mechanics during gait. Therapeutic effects i.e. without FES were observed in clinical measures of gastrocnemius spasticity, community mobility and balance skills in the treatment group at post treatment and follow-up. This study supports the use of FES applied during daily walking activities to improve gait mechanics as well as to address community mobility issues among children with unilateral spastic cerebral palsy.